2012
DOI: 10.1111/j.1754-4505.2012.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health referral trigger tools for people living with HIV

Abstract: This study validated and compared two different Oral Health Referral Trigger Tools in the form of brief (3-item and 5-item) questionnaires designed to identify people living with HIV (PLHIV) with symptoms of oral disease requiring a dental referral from other health professionals. It was composed of a self-completed questionnaire and oral screen by a dentist of a convenience sample selected from PLHIV attending two outpatient clinics for routine nondental care for HIV infection. The dental exam was completed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…In addition, studies show that patients on HAART have a lower occurrence of carious surfaces than those that are not. This is because patients that tend to adhere to treatment are more likely to seek health care and therefore, more often visit the dentist and the dental treatment is performed completely …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies show that patients on HAART have a lower occurrence of carious surfaces than those that are not. This is because patients that tend to adhere to treatment are more likely to seek health care and therefore, more often visit the dentist and the dental treatment is performed completely …”
Section: Discussionmentioning
confidence: 99%
“…This is because patients that tend to adhere to treatment are more likely to seek health care and therefore, more often visit the dentist and the dental treatment is performed completely. [27][28][29] Historically, in Brazil, the adult population has been intended for emergency dental services, mostly caused by pain, which usually results in missing teeth.…”
Section: Discussionmentioning
confidence: 99%
“…This was a subanalysis of a study on Validation of Oral Health Referral Trigger Tools (VOHRTT) for nondental clinicians managing PLHIV. Preliminary findings of VOHRTT study have been previously reported 9 …”
Section: Methodsmentioning
confidence: 69%
“…A convenience sample of HIV-positive individuals (n = 62) attending the University of California, Los Angeles outpatient HIV Clinical AIDS Research and Education (CARE) clinic from February 01 to May 31, 2017 completed a short questionnaire, developed using validated symptom queries shown to correlate with dentist-assessed periodontal disease (Carey, Ackerie, Houtzager, Purnomo, & Jeganathan, 2014).…”
Section: Prevalence Of Dental Symptoms and Access To Dental Care In Amentioning
confidence: 99%